IMPLEMENTASI PROGRAM PEMBERDAYAAN MASYARAKAT DALAM PENANGGULANGAN KEMISKINAN DI KECAMATAN KENDAHE KABUPATEN KEPULAUAN SANGIHE (Suatu Studi Pada Kegiatan Simpan Pinjam Perempuan) - TOPUH, SRI DARYANTI; RARES, JOICE; KIYAI, BURHANUDDIN (Sam Ratulangi University, 2014)
Along with the implementation of PNPM Mandiri Rural, Kec.Kendahe is one of thevillages that became the target of PNPM Rural, which is located in District Kendahe, Sangihe, InKec.Kendahe has established a program called Women's Savings and Loans (SPP) which aims toempower women in the village. In the implementation of PNPM MP frequent problems that led to theimplementation of PNPM MP is not going well.This study aims to determine how the implementation of the National Program for CommunityEmpowerment for Rural and To determine constraints faced in the implementation of the Group Savingsand Loans Women In District Kendahe This study took place in the District Kendahe Sangihe and type ofstudy is a qualitative study with a sample of 15 respondents / informants.The result is that the Implementation Program for Community Empowerment in Poverty Kendahedistricts are judged on seven indicators of assessment in general it turns out that the implementation of theProgramme of Activities of savings and loans in the District Kendahe women has shown a pretty goodrate.From the overall results of the above studies it can be deduced that in the District kendahe inmanaging micro-credit activities of women in poverty alleviation in the district has been successful in itsimplementation because it can be viewed from many members of the group were successful in managingbusinesses that received loans from UPK resulting increase in the standard of living in the family.Keywords: Community development programs, Poverty Reduction